Formulation and Evaluation of Controlled-Release Diuron as Pre-Emergence Herbicide - Mazlan, Norida (1999)
Controlled-release formulations of diuron were prepared in the laboratory using the concept of physical matrix utilizing sodium alginate and kaolin. The release rates of diuron from the formulations were determined by chemical assay and bioassay. In the chemical assay, using high performance chromatography with UV detector, significant differences in release rates between formulations were observed from 3 to 7 days after the granules were placed into distilled water. The formulation having a 1:1 ratio of alginate to kaolin with 1 mm granule size showed the fastest release of diuron while release from the 2 mm granules was slower. The release of diuron from the formulations reached a maximum level of 27% at 30 days after placement in water this same rate of release was maintained up to 60 days after the treatment. Increasing the proportion of kaolin to sodium alginate in the controlled-release formulation reduced the release rate of active agent. Bioassays were conducted in the glasshouse to study the release rates of diuron using Brassica rapa seedlings as bioindicator. The controlled-release formulations showed slower release than the conventional formulation at the beginning of the treatments. At 3 weeks after treatment, there was no significant difference in the mortality of the seedlings between the conventional formulation and controlled-release formulations. However, the controlled-release formulations gave significantly higher seedling mortality compared to the conventional formulation at 16 weeks after the treatments. The same results were observed up to 24 weeks after the treatment when the controlled-release formulations caused between 40 to 70% mortality, while the conventional formulation treatment caused only 6% mortality. Among the controlledrelease formulations, the A K-2 formulation (1:1, alginate to kaolin) was found to give the best control with the highest percentage mortality of the seedlings.